On the Heating of the Slow Solar Wind by Imbalanced Alfvén-wave Turbulence from 0.06 to 1 au: Parker Solar Probe and Solar Orbiter Observations - Sofiane Bourouaine; Jean C. Perez; Benjamin D. G. Chandran; Vamsee K. Jagarlamudi; Nour E. Raouafi; Jasper S. Halekas (The Astrophysical Journal Letters)
In this work we analyze plasma and magnetic field data provided by the Parker Solar Probe and Solar Orbiter missions to investigate the radial evolution of the heating of Alfvénic slow wind by imbalanced Alfvén-wave (AW) turbulent fluctuations from 0.06 to 1 au. in our analysis we focus on slow solar-wind intervals with highly imbalanced and incompressible turbulence (i.e., magnetic compressibility C _B = δ B / B ≤ 0.25, plasma compressibility C _n = δ n / n ≤ 0.25, and normalized cross helicity σ _c ≥ 0.65). First, we estimate the AW turbulent dissipation rate from the wave energy equation and find that the radial profile trend is similar to the proton heating rate. Second, we find that the scaling of the empirical AW turbulent dissipation rate Q _W obtained from the wave energy equation matches the scaling from the phenomenological AW turbulent dissipation rate Q _CH09 (with Q _CH09 ≃ 1.55 Q _W ) derived by Chandran & Hollweg based on the model of reflection-driven turbulence. Our results suggest that, as in the fast solar wind, AW turbulence plays a major role in the ion heating that occurs in incompressible slow-wind streams.